DESAIN RUANG ADAPTIF SEBAGAI RESPON KEBUTUHAN GAYA HIDUP MASYARAKAT MASA KINI PADA PERANCANGAN PUJASERA - Linggar Gusti Rhezafabella; Vincentius Totok Noerwasito; Ngurah Antaryama (Jurnal Arsitektur ARCADE, 2024)
Abstract: The culinary industry in Indonesia is increasing following developments in today's people's lifestyles, the popularity of food courts is also increasing and is available in public, educational and health facilities. Food courts are generally homogeneous and not adaptive considering the lifestyle and behavior of today's society. Adaptive architecture is responsive in presenting spatial and environmental aspects which can follow the lifestyle behavior of today's society. The adaptive food court design aims to present a functional space with informative circulation access to suit the lifestyle behavior of people who work anywhere and like something practical. The adaptive food court will be designed using a force based framework method. The force method begins by looking at issues related to the context of today's people's lifestyles, people's culture of behavior, and the need for an adaptive space that adapts to the needs of its users. Then it is processed by looking at the assets and constraints of the surrounding environment, responding to forces by arranging elements, re-confirming the adaptive aspects of the elements and then proposing a design. The design results produce fin-like openings on the facade as a marker of time. Space facilities are divided based on characteristics with elevation as a differentiator. Patterns on the floor as signs for circulation. Green open space as a means of relaxation and natural air circulation. Arrangement of furniture in space at a distance to maintain user privacy.Keyword: adaptive space, food court, lifestyleAbstrak: Industri kuliner di Indonesia semakin meningkat mengikuti perkembangan gaya hidup masyarakat masa kini, popularitas pujasera juga semakin meningkat dan tersedia pada fasilitas umum, pendidikan, hingga kesehatan. Pujasera pada umumnya bersifat homogen dan tidak adaptif melihat gaya hidup perilaku masyarakat masa kini. Arsitektur adaptif bersifat responsif menghadirkan spasial dan lingkungan yang dapat mengikuti perilaku gaya hidup masyarakat masa kini. Desain pujasera adaptif bertujuan untuk menghadirkan sebuah ruang yang fungsional dengan akses sirkulasi informatif menyesuaikan perilaku gaya hidup masyarakat yang bekerja dimana saja dan menyukai sesuatu yang praktis. Pujasera adaptif akan dirancang dengan metode kerangka kerja force based framework. Metode force dimulai dengan melihat isu terkait context gaya hidup masyarakat masa kini, culture perilaku masyarakat, dan needs sebuah ruang adaptif yang menyesuaikan kebutuhan penggunanya. Kemudian diproses dengan melihat asset dan constraint lingkungan sekitar, merespon force dengan menyusun elemen, memastikan kembali aspek adaptif pada elemen dan kemudian mengusulkan desain. Hasil perancangan menghasilkan bukaan seperti sirip pada fasad sebagai penanda waktu. Fasilitas ruang terbagi berdasarkan sifat dengan elevasi sebagai pembeda. Pola pada lantai sebagai tanda untuk sirkulasi. Ruang terbuka hijau sebagai sarana relaksasi dan sirkulasi udara alami. Â Penataan furnitur pada ruang berjarak untuk menjaga privasi pengguna.Kata Kunci: gaya hidup, pujasera, ruang adaptifÂ